(untitled) (Journal of actual problems of jurisprudence, 2024)
Cryptocurrency is an intangible digital asset which has a cryptographic identity and uses a decentralized system. The intangibility and cryptographic identity will tie the existence of cryptocurrency and the encryption key which is used to produce a digital signature that is later used to conduct a transaction. In general, an intangible asset will seek how a legal system regulates the existence, transfer, and transaction of the asset. In this case, it shall apply the principle of lex rei sitae. This Latin phrase means the law of the land where the asset is situated. As for cryptocurrency, the digital asset is situated in a certain place on a server which is owned by the owner of the asset or a third party. The destination and transfer of that asset will be governed by the law where the asset is situated. This is an application of private international law which will determine the fundamental law or general principle law of some countries in relation to foreign law and legal-based decisions on a case regarding the legal interest between private parties that come from different countries and different country laws. The existence of the asset, transfer, transaction, and the possible dispute between the parties will be determined by the law that applies to the owner of the asset. If the owner is domiciled in a country with a different law than the asset is situated, it is possible to change the place or apply the law of the owner’s country. This is called renvoi. This is a very complex law application, especially for the global scope of cryptocurrency transactions, so it is necessary to further discuss the application of it to the dispute involving the foreign party. This work does not cover various legal issues related to cryptocurrencies but considers only private international law aspects. It is based on the assumption that cryptocurrencies have the potential to evidence intangible assets and can be subject to proprietary rights. Keywords: private international law, virtual assets, digital assets, Unidroit, conflict of laws